The house by the lake : a story of Germany - Harding, Thomas 1968- (William Heinemann, 2015)
In the summer of 1993, Thomas Harding travelled to Germany with his grandmother to visit a small house by a lake on the outskirts of Berlin. It had been her 'soul place' as a child, she said - a holiday home for her and her family, but much more - a sanctuary, a refuge. In the 1930s, she had been forced to leave the house, fleeing to England as the Nazis swept to power. The trip, she said, was a chance to see it one last time, to remember it as it was. But the house had changed. Nearly twenty years later Thomas returned to the house. It was government property now, derelict, and soon to be demolished. It was his legacy, one that had been loved, abandoned, fought over - a house his grandmother had desired until her death. Could it be saved? And should it be saved? He began to make tentative enquiries - speaking to neighbours and villagers, visiting archives, unearthing secrets that had lain hidden for decades.